Researching lesser-explored issues in counselling and psychotherapy (Karnac Books : Made available through hoopla, 2016)
Peter Madsen Gubi and Valda Swinton have brought together important research into little-explored topics that are applicable to the field of counseling and psychotherapy. Each contributor has undertaken qualitative research into their chosen topic, and this book disseminates that research in a highly accessible manner. The aim of the volume is to inform counselors and psychotherapists, and those in allied professions who support and care for people, towards developing a greater awareness of issues they may encounter. These include sexuality after breast cancer in young, single women; the impact of pregnancy loss on women who delayed childbirth and remain childless; adult reflections on being an only child; processing parental rejection through personal development; the nature of school-based counseling; the impact of emotional labor on secondary school teachers; and the impact of inappropriately referred clients on counseling trainees in placement.